Outcome measures for assessing the effectiveness of physiotherapy interventions on equinus foot deformity in post-stroke patients with triceps surae spasticity: A scoping review. - Isabella Campanini; Maria Chiara Bò; Maria Chiara Bassi; Benedetta Damiano; Sara Scaltriti; Mirco Lusuardi; Andrea Merlo (PLoS ONE, 2023)
Objective Equinus foot deformity (EFD) is the most common deviation after stroke. Several physiotherapy interventions have been suggested to treat it. However, studies evaluating the efficacy of these treatments vary widely in terms of assessment modalities, type of data analysis, and nomenclature. This scoping review aimed to map current available evidence on outcome measures and the modalities employed to assess the effectiveness of physiotherapy programs for the reduction of triceps surae (TS) spasticity and EFD in patients with stroke. Methods Scoping review methodological frameworks have been used. Three databases were investigated. Primary literature addressing TS spasticity in adult patients with stroke using physiotherapy interventions was included. Findings were systematically summarized in tables according to the intervention used, intervention dosage, control group, clinical, and instrumental outcome measures. Results Of the 642 retrieved studies, 53 papers were included. TS spasticity was assessed by manual maneuvers performed by clinicians (mainly using the Ashworth Scale), functional tests, mechanical evaluation through robotic devices, or instrumental analysis and imaging (such as the torque-angle ratio, the H-reflex, and ultrasound images). A thorough critical appraisal of the construct validity of the scales and of the statistics employed was provided, particularly focusing on the choice of parametric and non-parametric approaches when using ordinal scales. Finally, the complexity surrounding the concept of "spasticity" and the possibility of assessing the several underlying active and passive causes of EFD, with a consequent bespoke treatment for each of them, was discussed. Conclusion This scoping review provides a comprehensive description of all outcome measures and assessment modalities used in literature to assess the effectiveness of physiotherapy treatments, when used for the reduction of TS spasticity and EFD in patients with stroke. Clinicians and researchers can find an easy-to-consult summary that can support both their clinical and research activities.